2023
DOI: 10.1111/jphd.12571
|View full text |Cite
|
Sign up to set email alerts
|

A certain protective effect of vitamin D against dental caries in US children and youth: A cross‐sectional study

Abstract: ObjectivesRecent studies reported that evidence of the association between caries and vitamin D was inconclusive. We investigated the relationship between dental caries and serum vitamin D levels in US children and youth aged 5–19 years through the National Health and Nutrition Examination Survey (NHANES). The purpose of this study was to analyze the relations between serum 25‐hydroxyvitamin‐D [25(OH)D] level and dental caries in children and youth.MethodsData were collected from the NHANES dataset performed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 48 publications
1
10
0
Order By: Relevance
“…This level of oral hygiene practice, however, did not translate into detailed reports on dental visits or the consumption of cariogenic foods and drinks. Pu et al [27] did not report on these influencing factors, yet the racial composition of their study population, with 13.6% identifying as Black, adds another layer to the demographic analysis of dental caries risk factors. Overall, patients with dark skin colors represented a proportion ranging from 9.8% in the study by Al-Darwish et al [25] to 33.1% in Akinkube et al study [21].…”
Section: Influencing Factorsmentioning
confidence: 91%
See 3 more Smart Citations
“…This level of oral hygiene practice, however, did not translate into detailed reports on dental visits or the consumption of cariogenic foods and drinks. Pu et al [27] did not report on these influencing factors, yet the racial composition of their study population, with 13.6% identifying as Black, adds another layer to the demographic analysis of dental caries risk factors. Overall, patients with dark skin colors represented a proportion ranging from 9.8% in the study by Al-Darwish et al [25] to 33.1% in Akinkube et al study [21].…”
Section: Influencing Factorsmentioning
confidence: 91%
“…Lastly, Pu et al [27] presented evidence of a protective role of Vitamin D, with an OR of 0.80 for caries among individuals with levels ≥ 50 nmol/L, reinforcing the beneficial impact of sufficient Vitamin D levels on dental caries risk. Kim et al [28], with 61.7% of the population being Vitamin D-insufficient, found a significant association between Vitamin D insufficiency and caries risk, with an OR of 1.29, as presented in Table 4 and Figure 2.…”
Section: Vitamin D and Dental Assessmentmentioning
confidence: 92%
See 2 more Smart Citations
“…Furthermore, severe vitamin D deficiencies have been shown to contribute to tooth hypo-mineralization and enamel hypoplasia [34,35]. Lower levels of vitamins A and/or D have been associated with higher prevalence of dental caries among adults and/or children in some epidemiological studies [36][37][38][39][40][41][42] but not others [43]. It has been suggested that vitamin D may protect against dental caries by modulating immunity in a manner that promotes eradication of cariogenic bacteria [36].…”
Section: Vitamins a And Dmentioning
confidence: 99%